(3GdcGajs - (3Gdcdjfj, GdQGRj, GdSdSdj, GdHZOGOj, CHh LYaQ, eMeO Hf jYbhH Hf ESMGb, J (B329 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B...(3cJGH GdWgGQI , HGH WghQjI GdeGA, MOKfj Ydj Hf EHQGgje Hf gGTe Yf CHjg Yf Gdfhadj Yf GdSchfj Yf CHj YHO Gddg Ydjg GdSdGe bGd bGd QShd Gddg Udi Gddg Ydjg hBdg (B" (3GdeGA ojWpqgQ hdG ojnWnqgQ (B" ..s
(3BNQgG (B:s
.. (3hCJGg QLd abGd Efce Cgd HjJ QMeI GNJUce Gddg JYGdi HgG abGd dg cPdc fMf hGdMeO ddg dG ofONd CMOG aj UdGdI hdG ofNQLg ef gOi (B...(3Je cJGH GdQhVI ef GdcGaj hgh BNQg(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B7\ 145s
(3GdPQjYI (B17\96s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs